2020 IEEE PES Innovative Smart Grid Technologies Europe (ISGT-Europe) 2020
DOI: 10.1109/isgt-europe47291.2020.9248895
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Battery Energy Storage in Electric Power Grids: Research and Practices

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…INSULAE (Maximizing the impact of innovative energy approaches in the EU islands) aims at fostering the deployment of technological solutions for the EU islands decarbonization. It will be achieved by the development and demonstration on three islands -Bornholm (Denmark), Madeira (Portugal), and Unije (Croatia) -of a set of interventions linked to seven replicable use cases and subsequent creation of tools for the replicability enhancement and the decision making support, such as island Action Plans and an Investment Planning Tool [6].…”
Section: ) Insulaementioning
confidence: 99%
“…INSULAE (Maximizing the impact of innovative energy approaches in the EU islands) aims at fostering the deployment of technological solutions for the EU islands decarbonization. It will be achieved by the development and demonstration on three islands -Bornholm (Denmark), Madeira (Portugal), and Unije (Croatia) -of a set of interventions linked to seven replicable use cases and subsequent creation of tools for the replicability enhancement and the decision making support, such as island Action Plans and an Investment Planning Tool [6].…”
Section: ) Insulaementioning
confidence: 99%
“…The assumptions underlying the assessment should be communicated to the decision maker and relevant uncertainties should be quantified and visualized. This approach can be contrasted with many of the optimization models proposed in the research literature that often returns only a single solution and does not provide the decision maker with insight into why this particular solution was selection or how sensitive the selection is to uncertainties [2].…”
Section: Framework For Active Distribution Grid Planningmentioning
confidence: 99%
“…In the research literature, on the other hand, a multitude of advanced optimisation methods have been proposed. However, considering BESS as one example of an active measure, a recent survey of the literature [2] found that these methods were rarely applied in a practical, long-term grid planning perspective. This makes it more challenging for distribution grid companies to employ such methods to assess costs, benefits and risks of active grid planning measures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is a large interest in PV prosumers with BESSs, with regards to scheduling and optimization [12]- [14]. In [15], the authors investigate the self-consumption of Swedish single-family households/dwellings, providing a sensitivity analysis of PV installation and battery of different sizes.…”
Section: Introductionmentioning
confidence: 99%